Local communities in cities as a subject of control over solving local issues - Alexander A. Larichev (Правоприменение)
The subject. This article is devoted to exploring the possibilities of formalizing the institution of local communities of citizens in urban areas, with the goal to more extensively involve local population in solving local issues, including controlling the organization of relevant processes.The purpose of the article to refute or confirm the hypothesis that local communities may exercise local control functions effectively to improve the quality of local services and reduce the number of local government officials.The methodology of the study includes methods of theoretical analysis, as well as legal methods, including the formal legal method.The main results and scope of their application. The activities of subjects of municipal ad‐ ministration – bodies and officials of local government, aiming at improvement of control over the solution of local issues are subject to difficulties, and institutional and organizational measures to develop the mechanism of municipal management in this case are not sufficient. The territorial reorganization of the city administration is also not justified ‐ the creation of intracity municipalities, as well as the formation of territorial subdivisions of the citywide administration is often costly and inefficient. At the same time, the population, being both a beneficiary of the solution of local issues, and, theoretically, the main subject of self‐government and a source of legitimation of municipal authority in cities, is excluded from the mechanism of control over the organization of relevant processes.The creation of local communities, in turn, could be an alternative to the proliferation of the apparatus of municipal bureaucracy in cities, providing legal guarantees for the implementation of citizens’  right to self‐government directly in territories of their residence. At the same time, local communities, unlike the territorial public self‐government, should be included into the general municipal management mechanism, which would ensure their financing at the expense of local administration. However, in contrast with the territorial bodies of city administrations, the functioning of local communities’ bodies should presup‐ pose mainly volunteer beginnings in their activities, whereas financial and material support should only assist in realization of their competence.Conclusions. The expansion of existing forms of control over the solution of local issues by local communities would contribute to improving the efficiency and quality of municipal services, the livelihood of the local population in urban areas.